Optimalisasi grand design pendidikan karakter sebagai upaya membangun karakter bangsa - Trisiana, Anita - (UNIVERSITAS SLAMET RIYADI, 2011)
Abstraksi : Chrakter is the way of thingking and behaving that characterize each individual to live and work, both within the scope of family, community, nation and state. Individuals that good character is an individual who can make decisions and be accountable for any consequences of the decisions he made. Law No.20 Year 2003 on National Education System mandates the importance of character formation as the basis for the development of the Indonesian nation. The character of a nation is a reflection of the condition of tires of education the GSA. The problems of Indonesia in various fields during this not out of character and values of society. If the current lot of criticism related to the character of the nations is necessary to attempt to solve problem one implementation of character education by making a grand desingn that need to be pursued further. Keyword : Optimalisasi, Grand Design, Pendidikan Karakter